2011
DOI: 10.1007/s00467-011-1846-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous EPO receptor activator therapy of anemia in children under peritoneal dialysis

Abstract: The short half-life of erythropoietin (rHuEPO) leads to repeated fluctuations in hemoglobin levels and the need for frequent administration. Continuous erythropoietin receptor activator (CERA) therapy has been approved for once or twice a month in adult dialysis patients. To evaluate the efficacy and safety of CERA therapy in the management of anemia in pediatric peritoneal dialysis (PD) stable PD children under twice-a-week EPO were converted to a subcutaneous CERA, scheduled every 2 weeks. The follow-up was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…An increasing number of studies have examined the outcomes (e.g., dose, frequency, side effects) of CERA therapy in children, which was developed as a longacting ESA [238,239]. The decrease in dosing frequency in children may be beneficial not only for reducing the burden on medical workers and increasing safety, as in adults, but also for improving medication compliance and reducing the burden on family members.…”
Section: Rationalementioning
confidence: 99%
“…An increasing number of studies have examined the outcomes (e.g., dose, frequency, side effects) of CERA therapy in children, which was developed as a longacting ESA [238,239]. The decrease in dosing frequency in children may be beneficial not only for reducing the burden on medical workers and increasing safety, as in adults, but also for improving medication compliance and reducing the burden on family members.…”
Section: Rationalementioning
confidence: 99%
“…There are currently limited data on the efficacy and safety of C.E.R.A. in pediatric patients, with two small studies reporting attainment of target hemoglobin levels without adverse drug reactions (10,11). This study was undertaken to determine the conversion factor that allows switching from other ESAs to C.E.R.A.…”
Section: Introductionmentioning
confidence: 99%
“…No randomized trials were identified regarding CERA use in children. Three observational studies evaluated CERA in 92 children [ 49 , 60 , 61 ]. Cano et al.…”
Section: Resultsmentioning
confidence: 99%
“…Cano et al. [ 61 ] studied 16 children over 6 months converted from rHuEPO to fortnightly subcutaneous CERA. They found Hb was maintained, although dosing varied significantly (0.5–2.9 µg/kg/dose).…”
Section: Resultsmentioning
confidence: 99%